1998
DOI: 10.1053/joca.1997.0099
|View full text |Cite
|
Sign up to set email alerts
|

Acute synovitis and intra-articular methylprednisolone acetate in ponies

Abstract: Based on the methods used, acute synovitis prevented changes induced by intra-articular MPA alone. Results suggested that the effect of intra-articular MPA on joint metabolism was different between inflamed and normal joints. Experimental studies must consider the effect of inflammation, as well as the potential to introduce in vitro culture artifacts when investigating the effect of intra-articular corticosteroids on chondrocyte function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 38 publications
3
51
0
Order By: Relevance
“…Previous studies have described changes in inflammatory proteins or inflammatory gene expression in horses with either a diagnosis of naturally occurring osteoarthritis or in which inflammation had been induced experimentally [3,[16][17][18][19][20][21][22][23]. This is the first in vivo report of changes in inflammatory gene expression, using microarray and qRT-PCR analysis, Equine Veterinary Journal 0 (2016) 1-9 © 2016 EVJ Ltd following administration of a corticosteroid to horses.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have described changes in inflammatory proteins or inflammatory gene expression in horses with either a diagnosis of naturally occurring osteoarthritis or in which inflammation had been induced experimentally [3,[16][17][18][19][20][21][22][23]. This is the first in vivo report of changes in inflammatory gene expression, using microarray and qRT-PCR analysis, Equine Veterinary Journal 0 (2016) 1-9 © 2016 EVJ Ltd following administration of a corticosteroid to horses.…”
Section: Discussionmentioning
confidence: 89%
“…However, the use of steroids in joints with pre-existing synovitis increases the expression of genes related to inflammation and the activity of catabolic enzymes (MacLeod et al 1998;Todhunter et al 1998). Classically, these drugs exert their antiinflammatory properties by inhibiting phospholipase A2 by producing anti-phospholipase proteins called lipocortins (Di Rosa et al 1984).…”
Section: Corticosteroids For Intra-articular Treatmentmentioning
confidence: 99%
“…Theses adverse outcomes can cause direct damage by inappropriate use of steroids in compromised joints (Chunekamrai et al 1989;Neustadt 2001). In fact, studies have shown that negative impact of COs on the matrix occur if high doses are used, when the treatment is repeated continuously, or when the drugs are used in healthy joints (MacLeod et al 1998;Todhunter et al 1998). On the other hand, Frean et al (2002) reported adverse responses even when low doses were administered.…”
Section: Corticosteroids For Intra-articular Treatmentmentioning
confidence: 99%
“…After an additional 72 h, the explants were rinsed twice with Gey's balanced salt solution and radiolabeled in medium containing [3H]-proline (SO pCi/ml) for 4 h. Explants were then placed in fresh medium without radiolabel for a 2 h chase period to maximize [3H]-proline incorporation. An important modification of the protocol in the current study as compared to our earlier reports [50,51] is that MPS at the appropriate experimental concentrations was maintained in the culture medium throughout the pulsdchase procedure. The explants were rinsed three times in PBS and once in sterile distilled water to remove unincorporated [3H]-proline and excess salts, transferred to glass vials for lyophilization, A.…”
Section: Collagen Synthesismentioning
confidence: 99%
“…Studies have shown that low-to-moderate doses of intraarticular or systemic corticosteroids ameliorate cartilage degeneration following adjuvant-induced polyarthritis in the rat [26] and experimental transection of the cranial cruciate ligament in the dog [43], and have no gross or microscopic adverse effects when used in moderate doses on horses with small osteochondral defects [ 17, 20,28]. Other important variables, both clinically and experimentally, appear to be the local joint environment and experimental procedures [38,51]. Using an in vivo model of synovitis, we showed that one dose of intraarticular MPA significantly decreased steady-state type I1 procollagen mRNA in articular cartilage [34].…”
mentioning
confidence: 99%